Dental Health Education Activity Management by Applying Self-Efficacy Theory with Social Support on Oral Health Care Behaviors of Grade 3 Students in Phanat Nikhom District Chonburi Province - บุญมี โศภิดา (Journal of Health Science of Thailand, 2022)
This research aimed to compare (1) mean scores on knowledge and oral health care behaviors before and after experiment between the control group and the comparison group, (2) mean scores on knowledge and oral health care behaviors before and after experiment within control group and the comparison group, and (3) mean scores on knowledge and oral health care behaviors before experiment, after experiment, and follow-up period within the control group. The sample consisted of 67 students in grade 3 students in Phanat Nikhom district Chonburi province which was divided into 34 students in the control group and 33 students in the comparison group. The research instruments were dental health education activities by applying self-efficacy theory with social support on oral health care behaviors, and questionnaire. Data were analyzed using percentage, mean, standard deviation, t-test, and a Repeated one-way ANOVA, which was statistically significant at 0.05 level. The research findings were as follows: (1) before experiment, mean scores on knowledge and oral health care behaviors of the control group and the comparison group were found no significant differences at the 0.05 level. After experiment, mean scores on knowledge and oral health care behaviors of the control group were found significantly higher than the comparison group at the 0.05 level, (2) mean scores on knowledge and oral health care behaviors of the control group after experiment were significantly higher than before experiment at the 0.05 level, while mean scores of the comparison group were found no significant differences at the 0.05 level before and after experiment, and (3) mean scores of the control group on oral health care knowledge after experiment and follow-up period were found no significant differences at the 0.05 level, but mean scores on oral health care behaviors of the control group at the follow-up period found significantly higher than after experiment at the 0.05 level